2012
DOI: 10.1016/j.ssresearch.2011.12.011
|View full text |Cite
|
Sign up to set email alerts
|

A cluster analysis of service utilization and incarceration among homeless youth

Abstract: Our paper examines service usage (e.g., shelter) as well as a typology of individuals who are most likely to use groupings of services among 249 homeless youth. Our results revealed that the majority of homeless young people have used food programs (66%) and street outreach (65%) on at least one occasion within the past year. Cluster analysis of services revealed four distinct groups: (1) basic survival service use, characterized by above average shelter, food, and outreach service use, but below average on co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(27 citation statements)
references
References 40 publications
1
26
0
Order By: Relevance
“…Kort-Butler and Tyler [31] conducted an analysis of homeless youth grouped by service utilization clusters and found that youth that only used services to get their basic needs met (i.e, shelters and outreach/food programs typical of drop-in centers) differed from those who did not use any services and from those who used multiple types of services available to them (e.g., counseling, mental health/substance use services). For example, those who only used services to get their basic needs met were more likely to report recent employment, older age, more nights on the street, more physical victimization of the street, and more criminal behavior than youth that reported very little use of any services at drop-in centers and elsewhere.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Kort-Butler and Tyler [31] conducted an analysis of homeless youth grouped by service utilization clusters and found that youth that only used services to get their basic needs met (i.e, shelters and outreach/food programs typical of drop-in centers) differed from those who did not use any services and from those who used multiple types of services available to them (e.g., counseling, mental health/substance use services). For example, those who only used services to get their basic needs met were more likely to report recent employment, older age, more nights on the street, more physical victimization of the street, and more criminal behavior than youth that reported very little use of any services at drop-in centers and elsewhere.…”
Section: Resultsmentioning
confidence: 99%
“…Researchers surveying 249 youth recruited from shelters and the street in three Midwestern cities found that youth are most likely to report use of outreach services typical to drop-in centers, such as food programs and street outreach, than other services like shelters and counseling services [31]. In a sample of 83 homeless youth interviewed in Chicago, IL and Los Angeles, CA, researchers found that the majority of youth used drop-in centers (58%) or food programs (54%), while less than half used counseling centers (40%) or shelters (36%) [32].…”
Section: Introductionmentioning
confidence: 99%
“…Drop-in centers offer services to address the basic needs of homeless youth such as food and hygiene, as well as case management and other programs to meet health and social service needs. Homeless youth are more likely to use drop-in centers than other types of services such as shelters (Kort-Butler & Tyler, 2012) and thus represent a site to reach homeless youth who may not seek care elsewhere (Pedersen, Tucker, & Kovalchik, 2016). Individuals were eligible if they were ages 18–25, seeking services at one of the drop-in centers, planned to be in the study area for the next month, and could be reached by e-mail or phone for follow-up.…”
Section: Methodsmentioning
confidence: 99%
“…Drop-in centers offer services to address the basic needs of homeless youth such as food and hygiene, as well as case management and other programs to meet health and social service needs. Homeless youth are more likely to use drop-in centers than other types of services such as shelters and AOD treatment (Kort-Butler & Tyler, 2012; Pergamit & Ernst, 2010); thus drop-in centers represent a place to reach those youth who may not seek care elsewhere (Pedersen, Tucker, & Kovalchik, 2016). …”
Section: Methodsmentioning
confidence: 99%